2020
DOI: 10.3389/fendo.2020.591217
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Perspectives on the Modulation of G-Protein Coupled Estrogen Receptor, GPER, Function

Abstract: Estrogens exert their physiological and pathophysiological effects via cellular receptors, named ERα, ERβ, and G-protein coupled estrogen receptor (GPER). Estrogen-regulated physiology is tightly controlled by factors that regulate estrogen bioavailability and receptor sensitivity, while disruption of these control mechanisms can result in loss of reproductive function, cancer, cardiovascular and neurodegenerative disease, obesity, insulin resistance, endometriosis, and systemic lupus erythematosus. Restoratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 153 publications
(160 reference statements)
1
14
0
Order By: Relevance
“…In breast, GPER expression and localization were important factors in tumor progression. In normal breast tissue, triple-negative or high histological grade breast tumors, Samartzis and colleagues [ 25 ] detected GPER into the nucleus whereas the level of cytoplasmic (but not nuclear) GPER protein was associated with better overall survival in luminal tumors [ 47 , 48 ]. GPER was known to initiate non-genomic estrogen signaling when localized into the plasma or the endoplasmic reticulum membrane whereas it directly bound gene promoters and modulated transcription into the nucleus [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In breast, GPER expression and localization were important factors in tumor progression. In normal breast tissue, triple-negative or high histological grade breast tumors, Samartzis and colleagues [ 25 ] detected GPER into the nucleus whereas the level of cytoplasmic (but not nuclear) GPER protein was associated with better overall survival in luminal tumors [ 47 , 48 ]. GPER was known to initiate non-genomic estrogen signaling when localized into the plasma or the endoplasmic reticulum membrane whereas it directly bound gene promoters and modulated transcription into the nucleus [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of the same mSR in different but strictly connected tissues in the TME also offers the possibility to intervene not only on the tumorigenic process itself but also in cancer-sustaining mechanisms. Synthetic and natural compounds able to bind mSRs here presented-apart from TRPM8 and GPER, whose molecular modulators were recently and excellently reviewed [203,204]-are listed in Table 1. PaCa-2 cells (pancreatic cancer) RACK1, alpha-Actinin-1 Reduced PGRMC1 interactions with the actin cytoskeleton [225] Human granulosa/luteal cell B-cell lymphoma 2 (BCL2) pathway Increased PGRMC1 monomeric form, increased proapoptotic Harakiri (Hrk) expression [226] Due to the relative novelty of mSRs as mediators of steroid signaling, studies on mSRactive compounds here presented were limited to the pre-clinical phase.…”
Section: Msrs As Drug Targetsmentioning
confidence: 99%
“…In addition, the expression of the same mSR in different but strictly connected tissues in the TME also offers the possibility to intervene not only on the tumorigenic process itself but also in cancer-sustaining mechanisms. Synthetic and natural compounds able to bind mSRs here presented—apart from TRPM8 and GPER, whose molecular modulators were recently and excellently reviewed [ 203 , 204 ]—are listed in Table 1 .…”
Section: Beyond Msrs Physiologic Rolementioning
confidence: 99%
“…GPER ligands may serve as novel pharmacological agents for treating human diseases. 36 Recent preclinical studies have shown that chronic administration of G1 could restore fat, glucose, and lipid homeostasis in mouse models. 37 This observation indicates that chronic GPER signaling has potential implications for the role of GPER in cancer, as metabolic syndrome is an independent risk factor for cancer.…”
Section: Gper Ligandsmentioning
confidence: 99%